2002
DOI: 10.1046/j.1365-2893.2002.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in patients with chronic hepatitis C

Abstract: In numerous studies of symptoms in patients with chronic hepatitis C there has been no systematic assessment of both fatigue and extrahepatic manifestations. Our objective was to assess the prevalence of fatigue in patients with hepatitis C virus (HCV) infection, and to identify associations between fatigue and clinical and biological hepatic and extrahepatic manifestations. We studied 1614 patients. Data were prospectively recorded during the first visit of patients infected with HCV and the prevalence of fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
141
0
14

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(165 citation statements)
references
References 30 publications
10
141
0
14
Order By: Relevance
“…33 Kramer et al 34 found significant fatigue in 120 untreated patients with CHC compared with healthy controls using the Fatigue Impact scale (49 versus 26 points) and the Brief Fatigue Inventory (3.0 versus 1.6 points; P Ͻ 0.001). In another study, Poynard et al 35 studied 1,614 patients with CHC to determine the association between fatigue and other clinical and biological extrahepatic manifestations of CHC. Fatigue was reported in 53% of patients and was disabling in 17%, 35 findings consistent with those of other studies in which the prevalence ranged from 50% to 67%.…”
mentioning
confidence: 99%
“…33 Kramer et al 34 found significant fatigue in 120 untreated patients with CHC compared with healthy controls using the Fatigue Impact scale (49 versus 26 points) and the Brief Fatigue Inventory (3.0 versus 1.6 points; P Ͻ 0.001). In another study, Poynard et al 35 studied 1,614 patients with CHC to determine the association between fatigue and other clinical and biological extrahepatic manifestations of CHC. Fatigue was reported in 53% of patients and was disabling in 17%, 35 findings consistent with those of other studies in which the prevalence ranged from 50% to 67%.…”
mentioning
confidence: 99%
“…Ao contrário de outras pesquisas (18)(19)(20)(21)(22)(23) , os resultados obtidos sugerem que o VHC, aparentemente, não desempenha nenhum papel na patogenia da fibromialgia, embora a falta de evidências aqui detectada não represente, necessariamente, a ausência da associação.…”
Section: Discussionunclassified
“…É fato que a fibromialgia constitui uma condição clínica freqüente (29) e, em estudos não-controlados, pode ser detectada em um número por vezes expressivo de pacientes, por mera questão de chance. Isso é o que se observa nas séries de casos obtidas a partir de uma amostra de pacientes cronicamente infectados (8,19,21,23) .…”
Section: Discussionunclassified
See 2 more Smart Citations